BALINESE DAUGHTER AND FEMINIST FATHER IN KOPLAK BY OKA RUSMINI - Anindya Kusuma Wardani (Lakon : Jurnal Kajian Sastra dan Budaya, 2019)
Balinese women and patriarchy are terms which closely related. They commonly appear at the same time. Can this stereotype be negotiated? In the work of Oka Rusmini’s Koplak, this phenomenon is tried to be negotiated. The appearance of women who are living freely from patriarchal culture is shown through the whole book. It makes a new perspective that patriarchy in Bali can be negotiated. The study aims to show that Balinese women are no longer related to the word patriarchy and they can live their life. Using Feminism theory, Koplak will be examined and seen from a feminist perspective. The analysis activity will use a descriptive-qualitative method. There are two results of the study, showing that nowadays Balinese women can live without a burden of patriarchal, even they have their culture. The culture can be negotiated and the appearance of the feminist father shows that the parent’s role in family can help Balinese women being free from patriarchal culture. It also shows that the word feminist is not always given to women.